ANÁLISE DE SILAGEM DE MILHO EM UMA PROPRIEDADE DO INTERIOR DE AUGUSTO PESTANA - RS - Brigo, Fabiana Santos Scherer; Martins, Luciane Ribeiro Viana; Zasso, Maria Aparecida De Carvalho; Pietczak, Luana; Buchar, Anderson; Rodrigues, Franciele Zborovski (Salão do Conhecimento, 2018)
Trabalho vinculado ao projeto de extensão